Demography of genets of clonal red seaweeds: current limitations and proposed solutions using genetic markers from experimental populations - Scrosati, Ricardo (HIDROBIOLÓGICA, 2017)
For clonal red seaweeds, the genet is defined as the thallus that develops from a single spore. The demography of genets for these organisms is poorly known. This results from the inability of visually detecting genets when ramets (fronds) are abundant, when separate thalli actually represent fragments of one original genet, and when holdfast coalescence occurs between neighboring genets. The use of genetic markers, such as allozymes and certain DNA regions, has allowed for the identification of genets in natural populations of clonal terrestrial plants. However, this may not work for natural populations of clonal red seaweeds, because several genets may be produced by asexual spores from the same individual, rendering those genets unidentifiable with certain genetic mrkers. A useful approach could be to study experimental populations under controlled laboratory conditions. The position and shape of genets could be monitored as they develop from genetically distinct spores, selected as such on purpose. Once the visual identification of genets becomes impossible due to the increasing density of ramets, mapping the different ramet genotypes shoul aloow for the continuous identification of genets. Some genetic variation could arise within genets through somatic mutation and genetic transportation. Rates of these processes are largely unknown for clonal seaweeds, so they should be first estimated to determine their potential effects on demographic studies based on genetic markers.